Overexpression of miR-210 ameliorates endothelial dysfunction in type 2 diabetic mice. (3rd October 2022) - Collado, A; Jiao, T; Zaccagnini, G; Yang, J; Carstrom, M; Martelli, F; Pernow, J; Zhou, Z
Abstract: Background: MicroRNA (miR)-210 plays a protective role in many cardiometabolic diseases, and its levels are reduced in whole blood, erythrocytes, and plasma in type 2 diabetes mellitus (T2DM). Our recent study demonstrated that miR-210 is downregulated in carotid artery plaques from patients with T2DM compared to non-diabetic patients. However, the functional role of miR-210 in endothelial dysfunction is not fully understood. Purpose: This study aimed to investigate the potential therapeutic value of miR-210 overexpression against T2DM-associated endothelial dysfunction. Methods: miR-210 transgenic mice (TG) at age of 8 weeks were subjected to Western Diet (WD) for 12 weeks. During the last 10 days of the diet regime, doxycycline or vehicle dissolved in drinking water was given to switch on miR-210 (miR-210/on) expression or keep it off (miR-210/off), respectively. Age-matched wild-type (WT) control mice received normal chow through the same period. Additionally, WT and T2DM db/db mice at age of 15–20 weeks received tail vein injections of miR-210 mimic or miR-210 scramble oligonucleotides. All animals were euthanized at the end of the treatment or 72h after the i.v. injections for determination of endothelial function by acetylcholine-induced endothelium-dependent relaxation (EDR) of isolated aortic segments from all groups of mice using wire myographs. The expression of protein tyrosine phosphatase 1B (PTP1B; a miR-210 target protein) and the levels of 4-hydroxynonenal (4-HNE; an oxidative stress marker) were measured in aortic segments by immunohistochemistry. All animal experiments and procedures were performed according to the guidelines by the U.S National Institutes of Health (NIH publication no 85–23, revised 1996). Results: EDR in aortic segments from miR-210/off TG mice fed WD and T2DM db/db mice injected with miR-210 scramble was significantly impaired compared to vessels from WT controls fed with regular chow (Fig. 1A, B). Of note, EDR was markedly improved or even restored in aortae from miR-210/on TG mice treated with WD and T2DM db/db mice injected with miR-210 mimic (Fig. 1A, B). Furthermore, the expression of PTP1B and the levels of 4-HNE, which is formed by lipid peroxidation, were significantly elevated in the aortae from miR-210/off TG mice treated with WD when compared to WT controls (Fig. 2A–D). The expression was attenuated in aortae of miR-210/on TG mice treated with WD compared to miR-210/off TG mice (Fig. 2A–D). There was a significant increase in the expression of PTP1B and a trend to increased 4-HNE levels in aortae of db/db mice injected with miR-210 scramble vs. control mice (Fig. 2E–H). A significant reduction in PTP1B but not 4-HNE was observed in db/db mice injected with miR-210 mimic (Fig. 2E–H). Conclusion: Genetic and pharmacological overexpression of miR-210 ameliorates endothelial dysfunction in mice fed with WD and db/db mice. Increasing miR-210 levels may become a potential treatment strategy. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swedish Heart and Lung Foundation